2022
DOI: 10.1111/eva.13376
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic divergence of plant–herbivore interactions along an urbanization gradient

Abstract: Urbanization alters abiotic and biotic environments across time and space (McDonnell & Hahs, 2015), as a result of the fragmentation of natural habitat and increased pollution, temperature, impervious surface area and numbers of invasive species (Grimm et al., 2008;Niemelä et al., 2011). These environmental changes have greatly altered species' population dynamics, community structure (Alberti, 2015) and species interaction networks (Delgado-V & French, 2012;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Changes in ecological interactions due to urbanization have the potential to cause adaptive evolution due to changes in the strength and direction of natural selection. Previous research has shown how variation in species interactions such as pollination and herbivory can drive the evolution of plant traits along urban to rural gradients (Breitbart et al, 2023;Irwin et al, 2018;Qu et al, 2022). However, few urban studies show evolutionary divergence driven by altered species interactions (Diamond & Martin, 2021), and we are unaware of any work examining how socioeconomic variation influences natural selection.…”
Section: Evolutionary Implicationsmentioning
confidence: 99%
“…Changes in ecological interactions due to urbanization have the potential to cause adaptive evolution due to changes in the strength and direction of natural selection. Previous research has shown how variation in species interactions such as pollination and herbivory can drive the evolution of plant traits along urban to rural gradients (Breitbart et al, 2023;Irwin et al, 2018;Qu et al, 2022). However, few urban studies show evolutionary divergence driven by altered species interactions (Diamond & Martin, 2021), and we are unaware of any work examining how socioeconomic variation influences natural selection.…”
Section: Evolutionary Implicationsmentioning
confidence: 99%
“…On the contrary, numerous studies tell us that phenotypic plasticity provides powerful adaptive and defensive capabilities in plants (Stotz et al 2021). Feeding by herbivorous insects is thought to be an important driving force for the generation of plant plasticity phenotypes, and the insect-plant arms race is a major driver of phytochemical diversity (Qu et al 2022). Feeding by herbivores not only leads to plasticity in the defensive traits of plants, but also has an influence on the floral traits of flowering plants, and indirectly interferes with plant pollination (Rusman et al 2019a(Rusman et al , 2022.…”
Section: Phenotypic Plasticity Is Essential For Plant Defense Against...mentioning
confidence: 99%
“…Field survey is also effective in clarifying the environmental factors that influence trait variation in field plants by examining the effects of measured factors on urbanisation-related trait variation. Thus, combining field survey and CGE is an effective approach to examining the evolution of plant traits in urban environments (Qu et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, combining field survey and CGE is an effective approach to examining the evolution of plant traits in urban environments (Qu et al . 2022).…”
Section: Introductionmentioning
confidence: 99%